Study on High-Temperature Synthesis Ejecting Technique of ZnO Nanomaterials. (November 2019) - Tang, Xiangjun; Li, Junshou; Zhao, Fang; Han, Kai; Song, Bin
Abstract: ZnO nanomaterials were prepared by self-propagating high-temperature synthesis ejecting technique with Al, Cu2 O, ZnO and SnO power reagents as raw materials. The structure and morphology were characterized by XRD, SEM and FTIR methods. The synthesis mechanism of ZnO nanomaterials was discussed. The results showed that single ZnO with hexagonal wurtzite structure was prepared by high-temperature combustion synthesis ejecting method. The products exhibited nanowire morphology, accompanied by granular and flaky morphologies. According to the analysis, the formation mechanism of ZnO nanomaterials is as follows: The reactant is heated to the molten liquid state by exothermic reaction of thermite powder, a self-ejecting system consisting of porous film with high melting point and low density, molten substances to be prepared and ejecting additives is formed by utilizing the difference of specific gravity and melting point between compounds. The substances to be prepared are ejected through the holes of the porous film by the gas released from the ejecting additives, and finally nanomaterials are obtained.